Biobased Materials and Their Composites for Oil Spill Treatment - Showkat, Ahmad Bhawani (Springer Nature, 2025)
This book provides solid, quantitative descriptions and reliable guidelines, reflecting the maturation and demand of the field and the development of bio-based methods for the treatment of oil spill. This book focuses on the different materials used for the oil spill treatment such as chitosan, carbon, lignin, carbohydrates and other bio-based materials (nanoparticles, membranes, aerogels, etc.). The coverage of book will highlight the most exciting applications in the field of oil spill treatment. This book is of interest to researchers working in the fields of material science of oil spill treatment, environmental chemistry, separation science, green and sustainable extraction techniques and bio-wastes.